A case study of improved cookstoves and clean fuel use by selected Nigerian Households. (June 2021) - Onah, Innocent; Nyong, Anthony; Ayuba, Kuje Haruna
Highlights: A pentagonal nexus exists between SDG 1, 2, 4, 7, 13, 15. The pentagonal nexus is hinged on food security, social, economic, energy, climate, and environmental factors. Integration of SDGs into NDCs and national development plans will strengthen climatic and environmental frameworks. Utilization of SDG policy analysis is required to direct investments to help build back better from the COVID-19 pandemic. A matrix of food security-based activities to better understand SDG synergies were recommended. Abstract: The implementation of the United Nations Sustainable Development Goals (SDGs) in Nigeria and many African countries seek evidence-based approaches to make business, health and socio-economic justification for increased public and private sector investments to achieve the goals. Yet, access to resources to engender food, energy, social, economic, and environmental security by over 62% of Nigerians living below the poverty line of 1.90 per day, remains a challenge. The aim of this paper is to use the SDG framework to analyze the inter-linkages between food security, social, economic, climate and environmental outcomes of a national clean cookstoves project that was effectively implemented in Nigeria between 2014 and 2018. The project distributed improved cookstoves and clean fuels to 1000 households with the aim of using it as a pilot to stimulate demand, contribute to the expansion of energy access for cooking, improve the livelihood of women and girls, reduce forest degradation and fuelwood-induced carbon emissions. Structured questionnaires were used to collect primary data from 161 households drawn from a randomly stratified experimental layout in Kwara state. Project variables were classified into economic security (SDG1), food security (SDG2), social security (SDG4), energy security (SDG7), climate variable (SDG13), and environmental sustainability (SDG15). Regression estimates reveal that all the representative SDG variables significantly impacted the food security of beneficiaries in the following order: SDG1 > SDG4 > SDG15 > SDG13 > SDG7. A conceptual framework consisting of pentagonal linkages was developed from Pearson correlation estimates. The study established a pentagonal nexus for SDG1, 2, 4, 7, 13, 15 hinged on food security, social, economic, energy, climate, and environmental factors. We suggest strengthening of climatic and environmental frameworks such as the integration of SDGs into Nationally Determined Contributions and long-term national development plans to drive food security. The study calls on the private sector to make use of SDG policy analysis to direct investments to help build back better from the COVID-19 pandemic. A matrix of food security-based policy, research, project, and knowledge activities were recommended to better understand SDG synergies.